Transsternal Thymectomy - Maurizi, Giulio; D'Andrilli, Antonio; Sommella, Lorenzo; Venuta, Federico; Rendina, Erino A. (The Thoracic and Cardiovascular Surgeon, 2015)
Thymectomy is a well-established indication for management of myasthenia gravis and it represents the most effective treatment for thymic tumors. The traditional surgical approach is median sternotomy. More recently, different less-invasive surgical approaches for thymectomy have been proposed as an alternative to open surgery. This article discusses the main technical aspects and results of literature.
Keywords: transsternal thymectomy; thymoma; myasthenia gravis